Software- and TDM-guided dosing of Meropenem promises high rates of target attainment in critically Ill patients - Chiriac, Ute; Richter, Daniel; Frey, Otto Roman; Röhr, Anka; Helbig, Sophia; Hagel, Stefan; Liebchen, Uwe; Weigand, Markus A.; Brinkmann, Alexander (Antibiotics, 2023)
Various studies have reported insufficient beta-lactam concentrations in critically ill patients. The optimal dosing strategy for beta-lactams in critically ill patients, particularly in septic patients, is an ongoing matter of discussion. This retrospective study aimed to evaluate the success of software-guided empiric meropenem dosing (CADDy, Calculator to Approximate Drug-Dosing in Dialysis) with subsequent routine meropenem measurements and expert clinical pharmacological interpretations. Adequate therapeutic drug exposure was defined as concentrations of 8-16 mg/L, whereas concentrations of 16-24 mg/L were defined as moderately high and concentrations >24 mg/L as potentially harmful. A total of 91 patients received meropenem as a continuous infusion (229 serum concentrations), of whom 60% achieved 8-16 mg/L, 23% achieved 16-24 mg/L, and 10% achieved unnecessarily high and potentially harmful meropenem concentrations >24 mg/L in the first 48 h using the dosing software. No patient showed concentrations <2 mg/L using the dosing software in the first 48 h. With a subsequent TDM-guided dose adjustment, therapeutic drug exposure was significantly (p ≤ 0.05) enhanced to 70%. No patient had meropenem concentrations >24 mg/L with TDM-guided dose adjustments. The combined use of dosing software and consecutive TDM promised a high rate of adequate therapeutic drug exposures of meropenem in patients with sepsis and septic shock.
Veröffentlicht: 27. Juni 2023
Gesehen am 25.08.2023